Da'wah in the digital era: Analysis of Husain Basyaiban's da'wah message in TikTok content - Amelia, Riska; Riyadi, Agus; Murtadho, Ali (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2024)
This study is motivated by the development of social media as a means of preaching, including Husain Basyaiban's Tiktok. This study aims to find out what da'wah messages are contained in the TikTok content in terms of the meaning of denotation, connotation, and myth. Therefore, this study is library research with a descriptive qualitative approach. The semiotic analysis used is the Roland Barthes model, a theoretical framework that examines signs and their meanings in cultural contexts. In this analysis, we identified and interpreted the signs (visual and textual elements) in Husain Basyaiban's TikTok video, considering their cultural and social contexts. The results of the analysis show that the video contains several meanings and messages, namely: mutual respect between religious communities, not insulting other people's beliefs, respecting other people's religious rituals when religion is insulted, fighting, being careful in protecting your beliefs, the importance of conscience in maintaining tolerance, Islam is the true religion, there is no prejudice against religions other than Islam, preaching is an obligation, and Muslims carry a great trust. Then, in Husain Basyaiban's TikTok video, researchers also found the meaning of the video's denotation, connotation, and myth. With the meaning obtained, this study implies the importance of disseminating da'wah content through social media. Social media like TikTok can display short moral content but with deep meaning.*****Studi ini dilatarbelakangi oleh perkembangan media sosial sebagai sarana dalam berdakwah diantaranya adalah Tiktok Husain Basyaiban. Studi ini bertujuan untuk mengetahui apa saja pesan dakwah yang terkandung dalam konten tiktok tersebut dilihat dari makna denotasi, konotasi, dan mitos. Oleh karenanya studi ini merupakan studi kepustakaan (library research) dengan pendekatan penelitian kualitatif deskriptif. Analisis yang digunakan merupakan analisis semiotika dengan model Roland Barthes. Hasil analisis menunjukkan bahwa di dalam video tersebut mengandung beberapa makna dan pesan, yakni: saling menghormati antar umat beragama, tidak menghina keyakinan orang lain, menghormati ritual agama orang lain, ketika agama dihina wajib dilawan, berhati-hati dalam menjaga akidah, pentingnya hati nurani dalam menjaga toleransi, Islam adalah agama yang benar, tidak berburuk sangka terhadap agama selain Islam, berdakwah merupakan suatu kewajiban dan umat Islam mengemban amanah yang besar. Kemudian dalam video tiktok Husain Basyaiban, peneliti juga menemukan makna denotasi, konotasi dan mitos dari video tersebut. Dengan makna yang didapat tersebut, studi ini mengimplikasikan pentingnya diseminasi konten dakwah melalui media sosial. Media sosial seperti TikTok dapat menampilkan konten moral singkat tetapi dengan makna yang mendalam.